Is it inverted U? Testing relationships between debt and growth: new evidence from smooth transition kink regression - Yamaka, Woraphon; Maneejuk, Paravee (Technological and Economic Development of Economy, 2025)
This study examines the inverted U-shaped relationship between public debt and economic growth rates in 44 countries, covering developed, developing, and underdeveloped economies, using data from 1970 to 2020. Unlike previous studies, which often use quadratic regression, threshold, and kink regression models that may not accurately capture the true relationship, we employ the smooth transition kink regression model for this analysis. Our results show that an inverted U-shaped relationship exists in 8 out of the 44 countries studied. The turning point of this relationship, where debt levels shift from beneficial to detrimental, ranges from 23.817% to 96.674%, highlighting the variance in optimal debt levels across different countries. These findings confirm the presence of the inverted U-shaped relationship but reject the notion of a universal turning point applicable to all countries.First published online 17 March 2025